2021
DOI: 10.1080/13549839.2021.1872513
|View full text |Cite
|
Sign up to set email alerts
|

Potential and limitations of innovative housing solutions in planning for degrowth: the case of Vienna

Abstract: Limiting socio-spatial inequalities can be considered a decisive goal for a degrowth agenda. At different territorial scales, planning and housing policies have been crucial to achieve this goal, in terms of both reaching high environmental standards and framing the social reproduction of inequality. This article focuses on the implications, in terms of socio-spatial inequalities, of innovative housing solutions oriented to a degrowth agenda. It aims to answer to the following research questions: what are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…However, authors exploring degrowth and housing have tended to focus on alternatives to existing mainstream housing, involving innovative design, technology, ownership, governance and finance (Nelson and Schneider, 2018). There are numerous case studies of innovative models such as co-housing, co-ownership, self-build, community land trusts, eco-communities, self-sufficiency, community gardening, squatting, rent or mortgage strikes and occupations of foreclosed buildings, and how they could contribute to degrowth (Cucca and Friesenecker, 2022; D’Alisa et al, 2015; Fournier, 2008; Nelson and Schneider, 2018; Weiss and Cattaneo, 2017). One review found that co-housing, a form that as yet provides for fewer than 1000 households in the UK (cohousing.org.uk), had received more research attention than projects affecting the hundreds of millions of existing homes, or larger-scale new development (Cosme et al, 2017).…”
Section: Housing Degrowthmentioning
confidence: 99%
“…However, authors exploring degrowth and housing have tended to focus on alternatives to existing mainstream housing, involving innovative design, technology, ownership, governance and finance (Nelson and Schneider, 2018). There are numerous case studies of innovative models such as co-housing, co-ownership, self-build, community land trusts, eco-communities, self-sufficiency, community gardening, squatting, rent or mortgage strikes and occupations of foreclosed buildings, and how they could contribute to degrowth (Cucca and Friesenecker, 2022; D’Alisa et al, 2015; Fournier, 2008; Nelson and Schneider, 2018; Weiss and Cattaneo, 2017). One review found that co-housing, a form that as yet provides for fewer than 1000 households in the UK (cohousing.org.uk), had received more research attention than projects affecting the hundreds of millions of existing homes, or larger-scale new development (Cosme et al, 2017).…”
Section: Housing Degrowthmentioning
confidence: 99%
“…Urban degrowth permits the spatial application of the principles of the degrowth movement in planning urban space, but the need for a dialogue between degrowth and urban planning has been largely neglected in existing degrowth narratives (Xue, 2021). Some studies have been published in the last few years addressing this recent field of research (Xue, 2015(Xue, , 2021Florentin, 2018;Lehtinen, 2018;Nelson & Schneider, 2018;Trainer 2019;Cristiano et al, 2020;Cucca & Friesenecker, 2021), and a review (Krähmer 2022). Wächter (2013) and Xue (2021) highlight the potential for urban planning to provide spatial instruments in a degrowth transformation, hence facilitating a down-scaling of the economy with environmental benefits and potentially, urban de-occupation.…”
Section: Urban Degrowth and Spontaneous Re-naturalizationmentioning
confidence: 99%
“…Innovation broadly engages the environmental, social, and economic parameters of sustainability, culminating in the analysis of commercial and technological activities in the market economy [29]. Accordingly, Cucca and Friesenecker [30] suggest that building healthy, comfortable, and ecologically sustainable residential areas is very important. In terms of construction, sustainable (housing) development requires a shift toward highquality buildings.…”
Section: Literature Review 21 Sustainable Affordable Housing Reviewmentioning
confidence: 99%
“…In terms of construction, sustainable (housing) development requires a shift toward highquality buildings. This requires the application of sustainable building and design techniques for energy conservation and generation and building standards, a reduction in the use of non-renewable materials, and the facilitation of the recycling of resources [30]. The wherefores are because construction has impacts through carbon emissions, climate change, waste generation, change of land use, and loss of biodiversity [31].…”
Section: Literature Review 21 Sustainable Affordable Housing Reviewmentioning
confidence: 99%
See 1 more Smart Citation